CCL21 expression pattern of human secondary lymphoid organ stroma is conserved in inflammatory lesions with lymphoid neogenesis. - Manzo, A; Bugatti, S; Caporali, R; Prevo, R; Jackson, D; Uguccioni, M; Buckley, C; Montecucco, C; Pitzalis, C (2007)
CCL21 is a homeostatic lymphoid chemokine instrumental in the recruitment and organization of T cells and dendritic cells into lymphoid T areas. In human secondary lymphoid organs (SLOs), CCL21 is produced by cells distributed throughout the T zone, whereas high endothelial venules (HEVs) lack CCL21 mRNA. A critical question remains whether the development of ectopic lymphoid tissue (ELT) in chronic inflammation recapitulates the features of SLOs. Thus, we systematically investigated in situ the cellular sources of CCL21 in SLOs and ELTs in several human diseases characterized by lymphoid neogenesis. By in situ hybridization and the use of combinatorial cell markers, we show that CCL21-producing vessels in inflamed tissues systematically display typical markers of lymphatic vessels, whereas, as in SLOs, ectopic HEVs do not synthesize detectable levels of CCL21. We also provide first-time evidence that a common pattern of CCL21 expression by CD45-negative myofibroblast-like cells localized in extra-HEV position and organized in a fibroblastic reticular network similarly characterizes human SLOs and organized ELTs. Altogether, our results demonstrate that in humans the pattern of CCL21 production in SLOs is maintained during inflammation and that the phenotypic and functional properties of stromal cells, found in SLO T-cell areas, are reproduced at ectopic sites.